Pleomorphic Invasive Ductal Carcinoma of the Breast in a Patient with Huntington's Disease - Sami Shousha (Hindawi Limited, 2014)
A pleomorphic invasive ductal carcinoma developed in a patient with Huntington's disease. The tumour showed marked nuclear pleomorphism and contained large number of bizarre tumour giant cells and abundant abnormal mitoses. Tumour cells showed nuclear vesicles and inclusions similar to those described in nuclei of neural cells in patients with Huntington's disease. The case suggests that, in some patients, tumour morphology may reflect specific individual features.